EFFECT OF RUPIAH EXCHANGE RATE, BI RATE AND MONEY SUPPLY ON THE NET ASSET VALUE OF SHARIA MUTUAL FUNDS: (Empirical Study on Sharia Mutual Funds Registered by the Financial Services Authority in 2016 - 2020) - Feliyawanti; R. Mohd. Zamzami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The purpose of this study is to analyze the effect of Rupiah Exchange Rate, BI Rate and Money in Circulation on the Net Asset Value of Islamic Mutual Funds. This research was conducted on Islamic mutual fund companies registered with the Financial Services Authority (OJK) in the period from 2016 to 2020. The sampling technique used in this study was a time series. This study used a quantitative approach and multiple linear regression analysis methods with SPSS version 25 and Microsoft Excel 2010. The results showed that the Rupiah Exchange Rate (Exchange Rate), BI Rate, and Money Supply simultaneously affected the NAV of Islamic Mutual Funds. The results of this study also show that partially the rupiah exchange rate and BI rate do not affect the NAV of Islamic Mutual Funds, and partially the money supply affects the NAV of Islamic Mutual Funds.